2017
DOI: 10.1016/j.jqsrt.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Spectral shapes of rovibrational lines of CO broadened by He, Ar, Kr and SF6: A test case of the Hartmann-Tran profile

Abstract: High signal-to-noise ratio spectra of the (3-0) band P(1) and P(17) lines of CO broadened by He, Ar, Kr and SF 6 were measured with a frequency-stabilized cavity ring-down spectroscopy system. For each collision-partner and both lines, multiple spectra were measured over pressures spanning nearly three decades up to 130 kPa. These data were analyzed with a multispectrum fitting procedure. Line shapes were modeled using the Hartmann-Tran (HT) profile with first-order line mixing as well as several other simplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 69 publications
2
11
0
Order By: Relevance
“…To further compare the two spectroscopic techniques, a calculation of the Allan deviation [36] for a simultaneously measured concentration of 101 ppm was conducted under identical conditions (Figure 11). At the integration time of 25 s, the detection limit of CW-CRDS reaches 35 ppb which is equivalent to that found in the literature [37,38] and for WM-DAS it is 161 ppb which is comparable to WMS [39,40] and is five times greater than that of CW-CRDS. The Allan deviation also indicates that the lowest stable precision for CW-CRDS needs less averaging time which is much less than the WM-DAS.…”
Section: Results and Discussion Of The Wide Range And Calibration-fresupporting
confidence: 76%
“…To further compare the two spectroscopic techniques, a calculation of the Allan deviation [36] for a simultaneously measured concentration of 101 ppm was conducted under identical conditions (Figure 11). At the integration time of 25 s, the detection limit of CW-CRDS reaches 35 ppb which is equivalent to that found in the literature [37,38] and for WM-DAS it is 161 ppb which is comparable to WMS [39,40] and is five times greater than that of CW-CRDS. The Allan deviation also indicates that the lowest stable precision for CW-CRDS needs less averaging time which is much less than the WM-DAS.…”
Section: Results and Discussion Of The Wide Range And Calibration-fresupporting
confidence: 76%
“…A multi-spectrum fitting procedure, developed previously in our group (e.g. [37,38]) was used to retrieve the line-shape parameters. For a given temperature, spectra of the same line, calculated for various Doppler width values, were simultaneously adjusted, the line-shape parameters being constrained to be the same for all spectra.…”
Section: Classical Molecular Dynamics Simulations For Co2-o2 and Analmentioning
confidence: 99%
“…It was shown that this profile can model measured transitions of various molecular systems to within a few 0.1 % (e.g. [5][6][7][8][9][10][11][12][13]). The international spectroscopic database HITRAN [14] now provides parameters of this profile when available.…”
Section: Introductionmentioning
confidence: 99%